Statistical Studies of Unincorporated Business - Klein, L. R.; Margolis, J. (The Review of Economics and Statistics, 1954)
U NINCORPORATED businesses comprise an interesting lacuna in the empirical knowledge of our economy, not to mention the unsatisfactory nature of theory which fails to account for the intertwining of household and firm behavior of those individuals who do not even have the legal structure of incorporation to separate their personal from their business activities. Lacking basic sources for statistical data on unincorporated business analogous to corporate income tax returns and accounting statements, economists have relied on scattered bits of information to piece together an incomplete picture of this sector. In this paper we shall examine data gathered from business respondents in past Surveys of Consumer Finances, conducted by the Survey Research Center for the Federal Reserve Board, to see what light can be shed on the structure of unincorporated business. As is well known, the Surveys of Consumer Finances are designed to give a statistical picture of the household or consumer sector of the economy and, in doing so, to provide in a rounded fashion various types of information on those households who have a whole or part interest in businesses. We have re-examined the questionnaire schedules from the I949-52 Surveys to extract as much information as possible on aspects of unincorporated business. The technical problems of using these schedules for the purposes at hand are taken up below. In each year's survey of 3,000-3,500 spending units, there are only 250-300 owners of unincorporated businesses, too few for most detailed analyses. In order to inaugurate work in this field on the basis of materials now available we have adopted, in many computations, the inadequate procedure of pooling the respondents from three or four surveys. We thereby get samples somewhat larger than 750 or i,ooo cases. The present phase of the study is, however, exploratory and preparatory to the ultimate conduct of a survey with a questionnaire tailored to our purposes and including an adequate number of cases for analysis. A motivating force behind this study of unincorporated business is the apparent existence of behavioral differences between business and other groups in the population. Statistical savings equations estimated from sample survey data indicate a hierarchical pattern in both marginal and average propensities to save: farmers are the highest savers; businessmen rank next; and non-entrepreneurial households are lowest. Various explanations have been advanced to account for the observed differences, and we shall consider these in some detail. The crucial issue is whether the differences are due to the savings and income concepts used or to alternative motivational forces and behavior patterns.' A by-product of this type of analysis is a contribution to the question whether the theory of behavior of businessmen can be compartmentalized into a theory of household behavior and a theory of firm behavior. If the compartmentalization is not possible, we are confronted with the necessity of developing a pooled theory of behavior. From the point of view of behavioral studies it may well be asked why we limit ourselves to unincorporated business. The reasons are largely pragmatic. The unincorporated sector is more of a terra incognita than either the farm or corporate sector. Legal differences in corporate organization carry some weight in distinguishing this type from unincorporated business, although it must be admitted that closely controlled small corporations may behave much like unincorporated enterprises of a comparable size. Many special features attached to farm enterprise, such as geographical location, government support, involvement in organized world markets, and so forth, lead us to exclude this sector from our present investigations.